2008
DOI: 10.1152/jn.90210.2008
|View full text |Cite
|
Sign up to set email alerts
|

Responses to Interaural Time Delay in Human Cortex

Abstract: Humans use differences in the timing of sounds at the two ears to determine the location of a sound source. Various models have been posited for the neural representation of these interaural time differences (ITDs). These models make opposing predictions about the lateralization of ITD processing in the human brain. The weighted-image model predicts that sounds leading in time at one ear activate maximally the opposite brain hemisphere for all values of ITD. In contrast, the π-limit model assumes that ITDs bey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 37 publications
6
25
1
Order By: Relevance
“…This is consistent with previous M/EEG studies, in which the MLR has shown sensitivity neither to ITDs (McEvoy et al 1994) nor to externalized percepts generated by head-related transfer functions (Junius et al 2007). It is also consistent with human fMRI data, which has shown that primary auditory cortex is highly sensitive to both ear of stimulation (Woods et al 2010;Stecker et al 2015;Gutschalk and Steinmann 2015) and interaural level differences (ILDs) Stecker et al 2015), but not ITD (von Kriegstein et al 2008;McLaughlin et al 2015). Although ITD sensitivity has been found in human auditory cortex, it is generally located in more posterolateral areas (von Kriegstein et al 2008;McLaughlin et al 2015) and in long-as opposed to middle-latency components of the AER (McEvoy et al 1993;Salminen et al 2009;Salminen et al 2010;Magezi and Krumbholz 2010;Gutschalk et al 2012) (for reviews, see Salminen et al 2012;Gutschalk 2014).…”
Section: Spatial Representation In the Auditory Pathwaysupporting
confidence: 92%
See 2 more Smart Citations
“…This is consistent with previous M/EEG studies, in which the MLR has shown sensitivity neither to ITDs (McEvoy et al 1994) nor to externalized percepts generated by head-related transfer functions (Junius et al 2007). It is also consistent with human fMRI data, which has shown that primary auditory cortex is highly sensitive to both ear of stimulation (Woods et al 2010;Stecker et al 2015;Gutschalk and Steinmann 2015) and interaural level differences (ILDs) Stecker et al 2015), but not ITD (von Kriegstein et al 2008;McLaughlin et al 2015). Although ITD sensitivity has been found in human auditory cortex, it is generally located in more posterolateral areas (von Kriegstein et al 2008;McLaughlin et al 2015) and in long-as opposed to middle-latency components of the AER (McEvoy et al 1993;Salminen et al 2009;Salminen et al 2010;Magezi and Krumbholz 2010;Gutschalk et al 2012) (for reviews, see Salminen et al 2012;Gutschalk 2014).…”
Section: Spatial Representation In the Auditory Pathwaysupporting
confidence: 92%
“…Although ITD sensitivity has been found in human auditory cortex, it is generally located in more posterolateral areas (von Kriegstein et al 2008;McLaughlin et al 2015) and in long-as opposed to middle-latency components of the AER (McEvoy et al 1993;Salminen et al 2009;Salminen et al 2010;Magezi and Krumbholz 2010;Gutschalk et al 2012) (for reviews, see Salminen et al 2012;Gutschalk 2014). In any case, the population-level representation of ITD at the level of the midbrain might be fundamentally different from that found in primary AC (Thompson et al 2006;von Kriegstein et al 2008;Belliveau et al 2014;Vonderschen and Wagner 2014;Yao et al 2015), though this is in need of further clarification.…”
Section: Spatial Representation In the Auditory Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…This lies well within the range of latencies of P1-N1 potentials observed in EEG and MEG studies, where the main sources have been identified at the Planum temporale (PT) and the Heschl’s gyrus (HG) (Liégeois-Chauvel et al 1994; Yvert et al 2005; Ross et al 2007b; Yamashiro et al 2011). Similarly, von Kriegstein et al (2008)—using functional magnetic resonance imaging (fMRI)—have shown that ITDs of 500 μs produced stronger activation in the hemisphere (PT) contralateral to the lateralized location, whilst ITDs of 1500 μs produced similar activation in both hemispheres (PT and HG). This suggests that both PT and HG are the main sources generating the IPM-FR.…”
Section: Discussionmentioning
confidence: 89%
“…Importantly, contralateral sensitivity to ILD cues evident in the blood oxygenation level-dependent (BOLD) signal represents binaural processes that cannot be explained by monaural intensity effects alone (15). As in the literature from animal models, reports of human cortical sensitivity to ITD have also been mixed, with some studies reporting moderate-strong contralateral dominance (16)(17)(18)(19), some weak contralateral dominance (13,14,20), and others a nonexistent sensitivity to ITD (21,22).…”
mentioning
confidence: 99%